Making shapes of glassy nematic sheets with three-dimensional director fields. (1st March 2019) - He, L.H.; Liu, R.H.
Abstract: Programmable shaping of glassy nematic sheets with three-dimensional director fields is explored. In contrast to planar inscriptions, the out-of-plane director orientations in these nematic sheets cause transverse shear strains upon heating or illumination. We quantify such an effect by extending the Reissner-Mindlin's nonlinear theory of elastic plates. The validity and necessity are examined via a special problem which has exact three-dimensional solution. Then we show, through a few typical examples, that the three-dimensional director fields can be exploited to create rich deformed shapes of the nematic sheets. Especially, some complicated morphologies can be programmed without producing resultant forces and moments.